Phytochemical Screening and Antioxidant Activity of Seven Native Species Growing in the Forests of Southern Chilean Patagonia - Merly de Armas-Ricard; Francisco Quinán-Cárdenas; Harold Sanhueza; Rodrigo Pérez-Vidal; Cristina Mayorga-Lobos; Oney Ramírez-Rodríguez (Molecules, 2021)
The genus Nothofagus is one of the most abundant in the subantarctic Patagonian forests. Five species inhabit these ecosystems, three evergreen (Nothofagus betuloides, Nothofagus dombeyi, and Nothofagus nitida) and two deciduous (Nothofagus pumilio and Nothofagus antarctica). This is the first report on the levels of secondary metabolites and the antioxidant capacity of Patagonian tree species growing in natural environments. The aim of this work was to carry out a phytochemical screening, to determine the antioxidant capacity, the sun protection factor, and the α-glucosidase and tyrosinase inhibitory activity of foliar extracts of the five previous species. Besides, Aristotelia chilensis and Berberis microphylla, two species of Patagonian shrubs growing in the same forests, were used as reference. N. dombeyi was the Nothofagus with the best antioxidant capacity. B. microphylla differed from all studied species. Moreover, the Nothofagus was split into two groups. N. betuloides and N. dombeyi are the most similar species to A. chilensis. The α-glucosidase was completely inhibited by all studied extracts. Furthermore, N. antarctica, N.pumilio, and N. nitida inhibited about 70% of the tyrosinase activity. All the results found in this study for the species of the genus Nothofagus support further research on their potential beneficial properties for human health.